2009
DOI: 10.1016/j.jmb.2008.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Amantadine-Bound M2 Transmembrane Peptide of Influenza A in Lipid Bilayers from Magic-Angle-Spinning Solid-State NMR: The Role of Ser31 in Amantadine Binding

Abstract: The M2 proton channel of influenza A is the target of the antiviral drugs amantadine and rimantadine, whose effectiveness has been abolished by a single-site mutation of Ser31 to Asn in the transmembrane domain of the protein. Recent high-resolution structures of the M2 transmembrane domain obtained from detergent-solubilized protein in solution and crystal environments gave conflicting drug binding sites. We present magic-angle-spinning solid-state NMR results of Ser31 and a number of other residues in the M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
188
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(208 citation statements)
references
References 57 publications
19
188
1
Order By: Relevance
“…Perhaps the most biologically relevant M2 structure comprises CD peptides in a DOPC/DOPE (dioleoylphosphatidylcholine/dioleoylphosphatidylethanolamine) bilayer at pH 7.5 [Protein Data Bank (PDB) ID: 2LOJ] (Sharma et al, 2010), although no drug molecule was bound. Recent drug-bound studies include a solid-state NMR structure in DMPC (dimyristoylphosphatidylcholine) bilayers with amantadine bound to the channel lumen (PDB ID: 2KQT) (Cady et al, 2009(Cady et al, , 2010, as well as solution structures of CD peptides in detergent micelles with four rimantadine molecules bound to a peripheral, membraneexposed binding site (PDB ID: 2RLF) (Schnell & Chou, 2008). Generally, solution structures show more compacted lumenal domains and a varied orientation of the C-terminal basic helices compared with solid-state structures.…”
Section: Iav M2mentioning
confidence: 99%
“…Perhaps the most biologically relevant M2 structure comprises CD peptides in a DOPC/DOPE (dioleoylphosphatidylcholine/dioleoylphosphatidylethanolamine) bilayer at pH 7.5 [Protein Data Bank (PDB) ID: 2LOJ] (Sharma et al, 2010), although no drug molecule was bound. Recent drug-bound studies include a solid-state NMR structure in DMPC (dimyristoylphosphatidylcholine) bilayers with amantadine bound to the channel lumen (PDB ID: 2KQT) (Cady et al, 2009(Cady et al, , 2010, as well as solution structures of CD peptides in detergent micelles with four rimantadine molecules bound to a peripheral, membraneexposed binding site (PDB ID: 2RLF) (Schnell & Chou, 2008). Generally, solution structures show more compacted lumenal domains and a varied orientation of the C-terminal basic helices compared with solid-state structures.…”
Section: Iav M2mentioning
confidence: 99%
“…Those 2 studies have generated controversies, especially about the mechanism of drug inhibition. Additional structural results have recently been published that add to the controversies surrounding inhibitor binding (23,24) and the closed-to open-state conformational transition (25).Channel activation may involve conformations not captured by the X-ray and NMR structures. Indeed, solid-state NMR (9,23,(26)(27)(28) and other studies have shown that the M2 TMD possesses significant conformational heterogeneity.…”
mentioning
confidence: 99%
“…Those 2 studies have generated controversies, especially about the mechanism of drug inhibition. Additional structural results have recently been published that add to the controversies surrounding inhibitor binding (23,24) and the closed-to open-state conformational transition (25).…”
mentioning
confidence: 99%
“…2, pore site 2). The authors noted, however, that the drug amine is too far from Ser31 hydroxyl groups (~4.5 Å) to form hydrogen bonds (Cady et al, 2009). Although the experimental and modeling studies above all suggested interaction between amantadine and AM2, none of them directly showed the location of the binding site inside the pore.…”
Section: Drug Inhibition and Ongoing Controversymentioning
confidence: 98%
“…However, this site would not be consistent with the above neutron diffraction data. Recently, Cady et al suggested based on chemical shift changes measured by solid-state NMR that amantadine binds to yet another site inside the channel (Cady et al, 2009). In this binding site, the drug amino group points to the N-terminal end of the channel and is located around Ser31 (Fig.…”
Section: Drug Inhibition and Ongoing Controversymentioning
confidence: 99%